An HR-EBSD and computational crystal plasticity investigation of microstructural stress distributions and fatigue hotspots in polycrystalline copper. (15th August 2016) - Wan, V.V.C.; Cuddihy, M.A.; Jiang, J.; MacLachlan, D.W.; Dunne, F.P.E.
Abstract: High resolution EBSD studies on a deformed copper polycrystal have been carried out to quantify the microstructural residual stress distributions, and those of stress state including triaxiality of importance in defect nucleation studies. Crystal plasticity analysis of a representative, similarly textured, model polycrystal has been carried out showing that the experimental distributions of microstructural residual stress components, effective stress, hydrostatic stress and stress triaxiality are well captured. The crystal model enables point-wise microstructural Schmid factors to be calculated both globally (ie with respect to the macroscopic remote loading) and locally from full knowledge of the grain-level stress state. Significant differences are demonstrated such that global Schmid analysis tends to overestimate slip activity and the frequency of high Schmid factors, indicating that the local microstructural heterogeneity is significant and caution is necessary in interpreting polycrystal behaviour using global Schmid factors. A stored energy criterion for fatigue crack nucleation indicates that preferential sites for fatigue crack nucleation are local to grain boundaries (as opposed to triple junctions), and that hard-soft grain interfaces where high GND densities develop are preferable. Graphical abstract: Cu polycrystal after 6% deformation (in y-diection) and unloaded showing (a) experimental in-plane residual shear stresses from HR-EBSD (legend in GPa) and (b) histograms of stress component differences calculated pointwise.